Mitochondrial FAD-linked Glycerol-3-phosphate Dehydrogenase: A Target for Cancer Therapeutics - Gurmit Singh (MDPI AG, 2014)
Imbalances in cellular redox state are frequently observed in cancer cells, and contribute significantly to cancer progression and apoptotic resistance. Hydrogen peroxide (H2O2) is one reactive oxygen species (ROS) that is produced in excess within cancer cells. In this study, we investigated the mitochondrial glycerol-3-phosphate-dependent (GPD2) ROS production in PC-3 cells and demonstrated the importance of excessive H2O2 production on their survival. By exploiting the abnormal H2O2 production of PC-3 cells, we initiated a high-throughput screening of the Canadian Compound Collection, composed of 29,586 small molecules, targeting the glycerophosphate-dependent H2O2 formation in PC-3 cells. Eighteen compounds were identified to have significant inhibitory activity. These compounds have not been previously characterized as inhibitors of the enzyme. Six of these compounds were further analyzed in PC-3 cells and dose response studies displayed an inhibitory and anti-oxidative potency that ranged from 1 µM to 30 µM. The results presented here demonstrate that inhibitors of mitochondrial GPD2 activity elicit anti-proliferative effects on cancer cells.